Sintesis dan Uji Antiinflamasi Senyawa (R)-3-(4-Florofenil)-1-fenil-5-(tiofen-2-il)-4,5-dihidro-1H-pyrazol Serta Pengaruhnya terhadap Kerusakan Lambung - Rullah, Kamal; Hasti, Syilfia; Hariani, Destawira; Utama, Putri Bela; Teruna, Hilwan Yuda; Zamri, Adel (Jurnal Penelitian Farmasi Indonesia, 2013)
An in-vivo anti-inflammatory study of pyrazoline compound synthesized from chalcone has been carried out using Paw Edema method.Compound (R)-3-(4-florofenil)-1-fenil-5-(tiofen-2-il)-4, 5-dihidro-1H-pyrazole was synthesized by milling method in alkaline condition,with no solvent addition and was conducted under room temperature. Characterization of the synthesized compound was determined using1H-NMR and HR-MS spectrometer. As for anti-inflammatory study, suspension of compound (R)-3-(4-florofenil)-1-fenil-5-(tiofen-2-il)-4,5-dihidro-1H-pyrazol was administrated orally to white female mice (Rattus novergicus) with doses 20, 40, 80 mg/kg bw, respectively. Theresult showed that the compound with doses 40 and 80 mg/kg bw exhibited insignificant difference compared with standard drugs Celecoxiband Piroksikam (p>0,05). Futhermore, all doses of compound did not cause any damage of stomach organ of mice, which is given the same“ulcer index” (Iu) with negative control (Iu 2,00). Meanwhile, ulcer index for Celecoxib of Iu 35,99 and Piroksikam of Iu 70,01.